2014
DOI: 10.1523/jneurosci.1948-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl-Serotonin Offers Neuroprotection through Inhibiting Mitochondrial Death Pathways and Autophagic Activation in Experimental Models of Ischemic Injury

Abstract: N-acetylserotonin (NAS) is an immediate precursor of melatonin, which we have reported is neuroprotective against ischemic injury.Here we test whether NAS is a potential neuroprotective agent in experimental models of ischemic injury. We demonstrate that NAS inhibits cell death induced by oxygen-glucose deprivation or H 2 O 2 in primary cerebrocortical neurons and primary hippocampal neurons in vitro, and organotypic hippocampal slice cultures ex vivo and reduces hypoxia/ischemia injury in the middle cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
106
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 65 publications
10
106
0
3
Order By: Relevance
“…This observation of L-NAT is not a direct mPT inhibitor contrasts with data on other agents, such as tricyclic antidepressants and phenothiazinederived antipsychotics identified in the library of 1040 compounds using a screen targeting mPT inhibitors (Stavrovskaya et al, 2004), but these data are consistent with our previous reports on methazolamide, melatonin, and N-acetyl-serotonin, three other potential therapeutic agents in the library of 1040 compounds and identified in the library of 1040 compounds by a screen targeting cytochrome c release (Wang et al, 2008;Wang, 2009;Zhou et al, 2014). Though they are neuroprotectants and inhibitors of cytochrome c release, they do not interfere with mPT induction in isolated mitochondria (Wang et al, 2008;Wang, 2009).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This observation of L-NAT is not a direct mPT inhibitor contrasts with data on other agents, such as tricyclic antidepressants and phenothiazinederived antipsychotics identified in the library of 1040 compounds using a screen targeting mPT inhibitors (Stavrovskaya et al, 2004), but these data are consistent with our previous reports on methazolamide, melatonin, and N-acetyl-serotonin, three other potential therapeutic agents in the library of 1040 compounds and identified in the library of 1040 compounds by a screen targeting cytochrome c release (Wang et al, 2008;Wang, 2009;Zhou et al, 2014). Though they are neuroprotectants and inhibitors of cytochrome c release, they do not interfere with mPT induction in isolated mitochondria (Wang et al, 2008;Wang, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…Its opening is a sign of mitochondrial dysfunction and results from biochemical stresses such as high concentrations of Ca 2+ ion or proapoptotic cytosolic proteins (Stavrovskaya et al, 2004;Rasola and Bernardi, 2011;Zhou et al, 2014). Mitochondrial swelling can be used as a marker to monitor the induction of mitochondrial permeability transition (mPT).…”
Section: L-nat Is Not a Mitochondrial Permeability Transition Inhibitmentioning
confidence: 99%
“…However, recent studies revealed that NAS could act as an agonist of TrkB and display neuroprotective properties in vitro and in vivo (Jang et al, 2010; Sompol et al, 2011). Meanwhile, Zhou et al demonstrated that NAS could also inhibit mitochondrial cell death pathways and autophagy activation following ischemic insults (Zhou et al, 2014). As a new derivative of NAS, HIOC has been proven to selectively phosphorylate TrkB with higher efficiency and is more stable than NAS (Shen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This process is necessary for normal cellular protein and lipid turnover and augmented following excitotoxic, ischemic and traumatic CNS injury (Diskin et al 2005; Guo et al 2014; Lin et al 2014; Ginet et al 2014; Zheng et al 2014; Zhou et al 2014). Recent studies reveal that during starvation induced autophagy, mitochondria supply membranes for autophagasome formation via association with autophagy mediating protein Atg5 and subsequent association with autophagasome protein microtubule-associated-protein-1 light chain 3 (LC3) (Hailey et al 2010) thus suggesting a critical role for mitochondria in the induction of autophagy.…”
Section: Autophagy/mitophagymentioning
confidence: 99%